Hungarian Monitoring, 2 November 1988 . [Magyar rádiófigyelő], 1988. november 2 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Bush, if elected, would like to meet Gorbachev - Poland: government-opposition talks postponed - Latin American summit - Post-elections situation in Israel - Gherasimov on Soviet-American relations - Uzbek mafia - UNESCO wants to sack delegation sent to Romania to study village destructions Domestic Affairs: - Interview with János Berecz on Central Committee debates to date: need for a new joint agreement - Press conference held in Foreign Affairs Ministry - “Hitel” (Credit) periodical published: interview with editor-in-chief - Democratic Alliance of Hungarian Gypsies formed - Protecting the interests of teachers - Football match fixing case continues Külpolitika: - Bush megválasztása esetén találkozni szeretne Gorbacsovval - Lengyelország: elmaradt a kormány és az ellenzék párbeszéde - Latin-amerikai csúcstalálkozó - A választás utáni helyzet Izraelben - Geraszimov a szovjet-amerikai kapcsolatokról - Az üzbég maffia - Az UNESCO küldöttséget kíván meneszteni Romániába a falurombolási program tanulmányozására Belpolitika: - Interjú Berecz Jánossal, a KB eddigi vitájáról. Új közmegegyezésre van szükség - Sajtótájékoztató volt a külügyminisztériumban - Megjelenik a Hitel c. folyóirat; interjú a főszerkesztővel - Megalakult a Magyarországi Cigányok Demokratikus Szövetsége - Pedagógusok érdekvédelme - Folytatódik a bunda-ügy